The old friends hypothesis: evolution, immunoregulation and essential microbial inputs - Rook, Graham A. W. (Frontiers in Allergy, 2023)
In wealthy urbanised societies there have been striking increases in chronic inflammatory disorders such as allergies, autoimmunity and inflammatory bowel diseases. There has also been an increase in individuals with systemically raised levels of inflammatory biomarkers correlating with increased risk of metabolic, cardiovascular and psychiatric problems. These changing disease patterns indicate a broad failure of the mechanisms that should stop the immune system from attacking harmless allergens, components of self or gut contents, and that should terminate inappropriate inflammation. The Old Friends Hypothesis postulates that this broad failure of immunoregulation is due to inadequate exposures to the microorganisms that drive development of the immune system, and drive the expansion of components such as regulatory T cells (Treg) that mediate immunoregulatory mechanisms. An evolutionary approach helps us to identify the organisms on which we are in a state of evolved dependence for this function (Old Friends). The bottom line is that most of the organisms that drive the regulatory arm of the immune system come from our mothers and family and from the natural environment (including animals) and many of these organisms are symbiotic components of a healthy microbiota. Lifestyle changes that are interrupting our exposure to these organisms can now be identified, and many are closely associated with low socioeconomic status (SES) in wealthy countries. These insights will facilitate the development of education, diets and urban planning that can correct the immunoregulatory deficit, while simultaneously reducing other contributory factors such as epithelial damage.